Problems of translation from English to Uzbek of names in "Cemetery Boys" by Ayden Thomas - Fayzimatova Nodirakhon Adkhamjon qizi; Sobirova Gulasal Ikhtiyorjon qizi (International Journal on Integrated Education, 2023)
The article examines the problems of translating the names of the Latin-American writer Ayden Thomas's work "Graveyard Children" from English to Ubek. Anthroponyms and toponyms, neologisms and lexicological problems are considered and analyzed in this work. Also, the example cited from the work was examined through morphological transformation and syntactic analysis.